2017
DOI: 10.1249/mss.0000000000001214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Training on Physiological and Hormonal Adaptions in Well-Trained Cyclists

Abstract: . Purpose: This study aimed to compare the effects of three different high-intensity training (HIT) models, balanced for total load but differing in training plan progression, on endurance adaptations. Methods: Sixty-three cyclists (peak oxygen uptake (V O 2peak ) 61.3 T 5.8 mLIkg j1 Imin j1 ) were randomized to three training groups and instructed to follow a 12-wk training program consisting of 24 interval sessions, a high volume of low-intensity training, and laboratory testing. The increasing HIT group (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Subsequently, we observed increased free-T following the addition of HIIT to this group ( 13 ). Conversely, Sylta and coworkers ( 19 ) reported a decrease in TT and free-T following four-week HIIT in well-trained young cyclists. These authors also reported that PPO increased concomitantly, which would appear counterintuitive given the pervasive belief that muscle power is positively influenced by testosterone.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Subsequently, we observed increased free-T following the addition of HIIT to this group ( 13 ). Conversely, Sylta and coworkers ( 19 ) reported a decrease in TT and free-T following four-week HIIT in well-trained young cyclists. These authors also reported that PPO increased concomitantly, which would appear counterintuitive given the pervasive belief that muscle power is positively influenced by testosterone.…”
Section: Introductionmentioning
confidence: 94%
“…HIIT has been shown to improve maximal aerobic power in masters athletes ( 7 ), and PPO and free-T in untrained older participants ( 13 , 20 ). Moreover, HIIT increased PPO, but decreased TT and free-T in young trained participants ( 19 ). However, the effect of HIIT on PPO, TT and free-T in masters athletes is currently unknown.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…High cortisol levels in response to anaerobic exercise possibly caused a potential for inhibition of testosterone production via steroid inhibition, and thus, cortisol induced a direct suppressive effect on testosterone steroidogenesis [55]. The T/C ratio has been identi ed as an indicator of anabolic/catabolic status during exercise [56]. An absolute ratio less than or equal to 0.35 × 10 − 3 or a decline in the free testosterone to cortisol ratio higher than 30% is suggested to be indicative of a negative catabolic state [57].…”
Section: Discussionmentioning
confidence: 99%
“…For example, four weeks of longer accumulated HIT duration (4 × 16 min) has been shown to elicit greater improvements in peak power output and peak oxygen consumption (V O2peak) compared to shorter duration HIT (4 × 4 min), despite lower heart rates (HR), blood lactate concentrations, ratings of perceived exertion (RPE) and a less pronounced steroid hormone response. 3 However, it is unclear how different interval training prescriptions influence athletes' health and immune status.…”
Section: Introductionmentioning
confidence: 99%